Advanced therapeutic strategies in patellar ligament tendinopathy: from etiology to clinical practice. A literature review. - Julia Stachowiak; Julia Sosin; Anna Pilarz; Maria Zwierzchowska; Aleksandra Sojka; Dariusz Salamon; Wojciech Domagała (Nicolaus Copernicus University in Toruń, 2024)
Introduction:  Tendinopathy of the patellar ligament, often referred to as "jumper's knee," is a significant health problem for athletes subjected to repeated knee strains. The condition, resulting from microtrauma and degeneration of collagen fibers, leads to chronic pain and impaired function of the patellar ligament.   Aim of the study: The aim of this study was to present current knowledge about new techniques to prevent and treat patellar tendinopathy. Analyzing current informations, understanding risk factors, and recognizing pathophysiology of patellar tendinopathy can prevent many sportsmen to withdraw from competitions.    Materials and methods: A systematic review of scientific and medical literature from the PubMed and Google Scholar databases was conducted. Results: A review of the literature has identified key risk factors for patellar ligament tendinopathy.  An analysis of available studies indicates that various therapeutic interventions, including shockwave therapy, eccentric exercise programs can provide pain relief and improve patellar ligament function. However, the effectiveness of these methods may vary depending on individual patient characteristics.   Conclusions: Recognition of risk factors, early education and prevention, and prompt introduction of treatment at an early enough stage of the disease allow for the best treatment results and rapid return of patients to sports activities before the onset of pain, and significantly improve patients' quality of life. These findings underscore the comprehensive nature of the management of patellar ligament tendinopathy, including both therapeutic and preventive interventions.   Keywords: patellar tendinopathy, orthopeadics, sport medicine, knee